Comprehensive Characterization of Circular RNAs in Ovary and Testis From Nile Tilapia - Zhong, Huan; Guo, Zhongbao; Xiao, Jun; Zhang, Hong; Luo, Yongju; Liang, Junneng (Frontiers in Veterinary Science, 2022)
Circular RNA (circRNA) is an endogenous biomolecule in eukaryotes. It has tissue-specific and cell-specific expression patterns and can act as a microRNA sponge or competitive endogenous RNA. Although circRNA has been found in several species in recent years, the expression profiles in fish gonad are still not fully understood. We detected the expression of circRNA in the ovary, testis and sex changed gonad of tilapia by high-throughput deep sequencing and circRNA specific computing tools. A total of 20,607 circRNAs were obtained, of which 141 were differentially expressed in testis and ovary. Among these circRNAs, 135 circRNAs were up-regulated and 6 circRNAs were down regulated in female fish. In addition, GO annotation and KEGG pathway analysis of the host genes of circRNAs indicated that these host genes were mainly involved in adherens junction, androgen production and reproductive development, such as ZP3, PLC, delta 4a, ARHGEF10, and HSD17b3. It is worth noting that we found that circRNAs in tilapia gonads have abundant miRNA binding sites. Among them, 935 circRNAs have a regulatory effect on miR-212, 856 circRNAs have a regulatory effect on miR-200b-3p, and 529 circRNAs have a regulatory effect on miR-200b-5p. Thus, our findings provide a new evidence for circRNA-miRNA networks in gonads in tilapia.